Evidence that male sea lamprey increase pheromone release after perceiving a competitor - Fissette, Skye D.; Bussy, Ugo; Huerta, Belinda; Buchinger, Tyler J.; Li, Weiming (Journal of Experimental Biology, 2020)
Sexual signals evolve via selective pressures arising from male–male competition and female choice, including those originating from unintended receivers that detect the signal. For example, males can acquire information from other males signaling to females and alter their own signal. Relative to visual and acoustic signals, less is known about how such communication networks influence chemical signaling among animals. In sea lamprey (Petromyzon marinus), the chemical communication system is essential for reproduction, offering a useful system to study a pheromone communication network that includes signalers and both intended and unintended receivers. Male sea lamprey aggregate on spawning grounds, where individuals build nests and signal to females using sex pheromones. We examined how exposure to a major component of the male pheromone, 3keto-petromyzonol sulfate (3kPZS), influenced male pheromone signaling, and whether females had a preference for males that altered their signal. Exposure to 3kPZS, at a concentration of 5×10−10 mol l−1, simulated the presence of other male(s) and led to increased 3kPZS release rates within 10 min, followed by a return to baseline levels within 30 min. Exposure also led to increases in hepatic synthesis and circulatory transport of pheromone components. In behavioral assays, females preferred the odor of males that had been exposed to 3kPZS; therefore, males likely benefit from upregulating 3kPZS release after detecting competition for mates. Here, we define how a specific pheromone component influences chemical signaling during intrasexual competition, and show a rare example of how changes in chemical signaling strategies resulting from male competition may influence mate choice.
Keywords: dept.che; peer-reviewed

Spatiotemporal Patterns in Profiles of Amino Acids Indicates They Are Unlikely Singular Olfactory Cues Underlying Natal Homing in Migratory Fishes - Kimmel, Jacob; Buchinger, Tyler; Tamrakar, Sonam; Huerta, Belinda; Larson, Douglas; Baker, Edward; Zorn, Troy; Scribner, Kim; Li, Weiming (Freshwater Biology, 2025)
ABSTRACT Migratory fishes are renowned for their ability to home to natal streams for spawning. Learned olfactory cues play a critical role in natal homing of Pacific salmon and other fishes, but the underlying chemical signature of streams remains poorly understood after decades of study. The molecules that convey a stream‐specific odour must differ among sites but remain constant over time. Among leading odorant candidates are amino acids; however, little research has assessed the spatial and temporal variability of amino acid profiles in streams. We report a comprehensive chemical study of dissolved amino acids as potential olfactory cues for homing by migratory fish. Specifically, we profiled amino acids in water from 23 streams in the upper Laurentian Great Lakes basin over 2 years. We investigated variation in amino acid profiles (1) among regions and rivers within a year, (2) between years and (3) among sites and across the seasons of migration and early life history within a stream. Liquid‐chromatography tandem mass spectrometry revealed nanomolar concentrations for most of the 20 L‐amino acids measured, above the levels detectable by studied migratory fishes. Moreover, amino acid profiles were temporally stable between 2 years and across an annual season from adult spawning migration through offspring early‐life development within a stream. However, spatial differences in amino acid profiles were evident primarily over large geographic distances (among regions) but not among tributaries within regions or among sites within a stream. Collectively, our results indicate dissolved amino acids may be consistent components of rivers' odorant profiles but suggest additional molecules are likely important for natal homing of migratory fishes to specific spawning sites. We suggest that future studies consider the combined importance of amino acids and molecules from other chemical classes. Understanding the chemical basis of olfactory‐guided natal homing is especially important as human activities could alter the odorant profiles of streams and thereby disrupt fish migrations and negatively impact population recruitment.
Keywords: Biology; Ecology; Evolutionary biology; Great Lakes; Homing (biology); Neuroscience; Olfaction; Olfactory cues; Olfactory system; Zoology; dept.che; navigation; olfactory imprinting; peer-reviewed; site fidelity; sturgeon